A Study to Investigate the Consumer’s Assessment of Brand Extension in the Emerging Market Pakistan. - Zahid, Misbah; Khan, Dr. Zargham Ullah; Butt, Jaffar Mehmood; Siddiq, Ms. Ujala; Wasim, Faryal (The journal of contemporary issues in business and government, 2020)
According to IMF outlook report 2015, Pakistan is included in the list of emerging economies of the world. Multinational corporations frequently use the brand extension marketing strategy in the emerging markets of the world. But to know how do consumers assess the brand extension is hampered by the limited studies in the context of developing markets. To understand this gap, the researcher in the present research study uses already established brand extension framework, namely Aaker model, and we extended this framework by adding one more factor which is „brand image‟. This new factor is added on the basis of previous literature. This new model is tested by using the consumers of Pakistan. The output reveals that brand image plays an important role in the consumers‟ evaluation of the brand extension in the context of emerging market. Managerial implications along with limitations and future research directions are also mentioned in the current paper.